Activating stimuli induce platelet microRNA modulation and proteome reorganisation - Cimmino, Giovanni; Tarallo, Roberta; Nassa, Giovanni; Filippo, Maria Rosaria De; Giurato, Giorgio; Ravo, Maria; Rizzo, Francesca; Conte, Stefano; Pellegrino, Grazia; Cirillo, Plinio; Calabrò, Paolo; Öhman, Tiina; Nyman, Tuula A.; Weisz, Alessandro; Golino, Paolo (Thrombosis and Haemostasis, 2015)
Platelets carry megakaryocyte-derived mRNAs whose translation efficiency before and during activation is not known, although this can greatly affect platelet functions, both under basal conditions and in response to physiological and pathological stimuli, such as those involved in acute coronary syndromes. Aim of the present study was to determine whether changes in microRNA (miRNA) expression occur in response to activating stimuli and whether this affects activity and composition of platelet transcriptome and proteome. Purified platelet-rich plasmas from healthy volunteers were collected and activated with ADP, collagen, or thrombin receptor activating peptide. Transcriptome analysis by RNA-Seq revealed that platelet transcriptome remained largely unaffected within the first 2 hours of stimulation. In contrast, quantitative proteomics showed that almost half of > 700 proteins quantified were modulated under the same conditions. Global miRNA analysis indicated that reorganisation of platelet proteome occurring during activation reflected changes in mature miRNA expression, which therefore, appears to be the main driver of the observed discrepancy between transcriptome and proteome changes. Platelet functions significantly affected by modulated miRNAs include, among others, the integrin/cytoskeletal, coagulation and inflammatory-immune response pathways. These results demonstrate a significant reprogramming of the platelet miRNome during activation, with consequent significant changes in platelet proteome and provide for the first time substantial evidence that fine-tuning of resident mRNA translation by miRNAs is a key event in platelet pathophysiology.
Keywords: Platelet activation; microRNA; RNA-Seq; quantitative proteomics; platelet system biology